Pengaruh terapi okupasi hidroponik terhadap tingkat harga diri penerima manfaat di unit rehabilitasi sosial eks psikotik - Romadhan, Robi; Estria, Suci Ratna; Etlidawati, Etlidawati; Prasetya, Rikhan Luhur (Holistik Jurnal Kesehatan, 2025)
Background: Mental health issues encompass a range of challenges, such as schizophrenia disorders that are often associated with decreased self-esteem in individuals. Patients with schizophrenia who have low self-esteem exhibit poor self-perception, feelings of worthlessness, and lack of self-confidence. Occupational therapy, as an effective non-pharmacological intervention, can improve self-esteem through targeted activities. Purpose: To assess the effect of hydroponic occupational therapy intervention on the level of self-esteem of beneficiaries in a social rehabilitation unit for ex-psychotics. Method: Pre-experimental one group pretest-posttest design, conducted on beneficiaries who experience low self-esteem at the Social Rehabilitation Unit for Ex-Psychotics "Martani" Cilacap. The sample was selected by total sampling and the instrument used was the Rosenberg Self-Esteem Scale. The data were tested for normality using Shapiro Wilk, after the normality test was normally distributed, then using the paired sample t-test. Results: The low self-esteem score before the intervention was 28.82 and after the intervention increased to 30.00. The normality test obtained a score before the intervention p-value of 0.105 and after the intervention it became 0.093. This figure shows that the data is normally distributed (> 0.05), meaning that there is an effect of occupational therapy intervention on the level of low self-esteem. Conclusion: Agricultural hydroponic occupational therapy intervention can increase the self-esteem score of patients with mental disorders. Hydroponic occupational therapy can help patients with mental disorders who have low self-esteem.   Keywords: Hydroponics; Low Self-Esteem; Occupational Therapy.   Pendahuluan: Masalah kesehatan mental mencakup berbagai tantangan, seperti gangguan skizofrenia yang sering dikaitkan dengan penurunan harga diri pada individu. Pasien dengan skizofrenia yang memiliki harga diri rendah menunjukkan persepsi diri yang buruk, perasaan tidak berharga, dan kurangnya rasa percaya diri. Terapi okupasi sebagai intervensi non-farmakologis dapat meningkatkan harga diri melalui aktivitas yang terarah. Tujuan: Untuk menilai pengaruh intervensi terapi okupasi hidroponik terhadap tingkat harga diri penerima manfaat di unit rehabilitasi sosial eks psikotik. Metode: Desain pre-experimental one group pretest-posttest, dilakukan kepada penerima manfaat yang mengalami harga diri rendah di Unit Rehabilitasi Sosial Eks Psikotik “Martani” Cilacap. Sampel dipilih secara total sampling dan instrumen yang digunakan adalah Rosenberg Self-Esteem Scale. Data di uji normalitas menggunakan Shapiro Wilk, setelah uji normalitas berdistribusi normal, maka menggunakan paired sample t-test. Hasil: Skor harga diri rendah sebelum intervensi adalah 28.82 dan setelah intervensi meningkat menjadi 30.00. Uji normalitas didapatkan skor sebelum intervensi p-value 0.105 dan setelah intervensi menjadi 0.093. Angka tersebut menunjukkan bahwa data berdistribusi normal (>0.05), artinya terdapat pengaruh intervensi terapi okupasi terhadap tingkat harga diri rendah. Simpulan: Intervensi terapi okupasi hidroponik pertanian dapat meningkatkan skor harga diri pasien gangguan jiwa. Terapi okupasi hidroponik dapat membantu pasien gangguan jiwa yang memiliki harga diri rendah.   Kata Kunci: Harga Diri Rendah; Hidroponik; Terapi Okupasi.